From College to Career: Career Readiness as a Driver of Work Readiness in Final-Year Students - Husna, Fatiya Halum; Susilawati, Ika Rahma; Shafira, Imas Salma; Wilujeng, Retno Ayu; Yohana, Tania; Kumalasari, Linda (Universitas Islam Negeri Raden Intan Lampung, 2025)
The number of higher education graduates entering the industrial workforce has declined. One of the factors influencing this issue is the low level of work readiness among university graduates. Work readiness is considered an important aspect that can contribute to increasing the absorption of graduates into the workforce. The low work readiness of university graduates needs to be addressed to prepare students to enter the job market in line with industry demands. This study aims to identify the relationship between career readiness and work readiness among final-year students. The subjects in this study were 90 final-year students from various majors. The study used a correlational quantitative approach, employing career and work readiness scales. The results of this study indicate that the hypothesis is accepted: career readiness is related to work readiness among final-year students (r = 0.590, p = 0.001, p < 0.05). The higher an individual's capacity to prepare for their career, the higher their work readiness. These findings suggest that forming a clear picture of one's career can be important in preparing to face the world of work.Keywords:Career readiness; college student; correlational analysis; work readiness